FAKTOR-FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM LAPORAN TAHUNAN PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Zanirah, Dewi Nur (Jurnal Ilmiah Mahasiswa FEB, 2016)
The growing issue of social responsibility (CSR) made the government created a law that requires Indonesian companies to conduct and disclose CSR. However, this law does not regulate how and what information should be disclosed. This makes the extensive of CSR disclosures to be diverse and disclosed simply because the company wants to establish a good image in the public eye. Given the circumstances, this study conducted with the aim to examine the factors that affect the extensive of CSR disclosure in annual report, including the company size, profitability, leverage, and commissioner board size. Samples used in this research are 78 companies listed on the Indonesian Stock Exchange in 2014 that meet the criteria of required  sample. By using multiple regression analysis, the results showed that company size, profitability, leverage, and commissioner board size simultaneously affect the CSR disclosure. While partially, the company size found to have positive influence, and leverage has a negative effect, while two other variables found no significant effect on CSR disclosure. The variable that has the most dominant influence on CSR disclosure is the company size. This research indicates that company size, profitability, leverage, and commissioner board size that is used in this research could explain 49,5% diversity of the extensive of CSR disclosure.Keywords : corporate social responsibility, corporate social responsibility disclosure, company size, profitability, leverage, commissioner board size